Efficiency improvement of assembly line: case study of bus seat manufacturer - Yeoh, Kim Hao (2013)
In this era of globalization, competition is becoming ever more intense. Manufacturing companies must not only compete locally but also on a global basis. Reducing manufacturing costs without sacrificing product quality is vital for the survival of manufacturing companies in a global market. With the increasing of market competition, the line balancing problem especially the assembly line balancing plays an important role for the industries to obtain the high quality and lowest cost. Assembly line plays a critical role in enabling a factory to deliver on time and at the right quantity and quality. This project main purpose is to assist in making an assembly line more efficient and productive through improving its line efficiency. The focus is on a bus seat assembly line. A manufacturing company faces difficulties in delivery on time. The core cause is the inefficiency of assembly line in the bus seat manufacturer. Therefore, the study will concentrate on manufacturer’s problem, which is efficiency of assembly line balancing for VIP seats. This research will attempt to overcome the problem by balancing its line and improved its efficiency. It also involves minimizing the number of stations and minimizing the balance delay time (sum of idle time).